Human and Non-Human Aspects in the Effectiveness of the Implementation of the Shopping Standard Analysis (ASB) on the Village Fund Project in Coastal Areas of North Minahasa Regency - Joubert B. Maramis; Victor P.K. Lengkong; Olivia S. Nelwan; Jantje L. Sepang (International Journal of Applied Business and International Management, 2019)
Research on the effectiveness of the application of ASB, especially in relation to village funds, is still rarely done. Many factors influence the effectiveness of the ASB preparation, but can be classified into two factors, namely the human and non-human aspects. Both of these aspects contribute to the effectiveness of the application of ASB. This study used exploratory factor analysis. The results of the analysis show that: (1) The dimensions or factors that shape human aspects in the effectiveness of the application of ASB are commitment factors, competency, adaptation, collaboration, technical capability, sub-district supervision function, organizational skills, village head development and planning ability. (2) Dimensions or factors that shape nonhuman aspects in the effectiveness of the application of ASB are Regulatory factors, Village Support, Administration, Wages / salaries and Village Institutions. (3) The dimensions or factors that shape the effectiveness of the application of ASB are factors: Standard cost of inputs, control tools, Abc (activity-based costing), according to village priorities, general validity, approval or determination and easy to update the data